دور حوكمة الشركات في تحسين جودة التقارير المالية في بيئة الأعمال السورية - إبراهيم, محمود; مكية, نغم أحمد فؤاد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هزت الفضائح المالية التي أدت إلى إفلاس العديد من الشركات والبنوك الكبرى على مستوى العالم،ثقة المساهمين والمودعين ورجال الأعمال، وأخذت قضية البحث عن سبل ووسائل للرقابة على أعمال تلك الشركات والبنوك، تفرض نفسها على الساحة الاقتصادية الدولية من أجل الحفاظ على حقوق المودعين والمساهمين، لضمان قيام المؤسسات المالية والاقتصادية بدورها، بعيدًا عن الفساد المالي والإداري. مما أدى في الآونة الأخيرة إلى ظهور ما يعرف بالحوكمة. و يهدف البحث لدراسة دور حوكمة الشركات في تحسين جودة التقارير المالية، وقد تم ذلك من خلال استبانة أجابت عليها عينة من المشاركين في سوق دمشق للأوراق المالية.واستخدام البرنامج الإحصائي (SPSS) في تحليل البيانات. The financial scandals that cause many companies and main banks allover the world to be bankrupt have shaken the confidence of shareholders, depositors and business men. To insure that the financial and economic institutions play its desirable role, searching for means of observing these companies and banks work became a predominant issue at the economic international arena in order to save the rights of the depositors and shareholders. As a respond to this request, a new term which is known as "Corporate Governance" has emerged in the latest period. The purpose of this study was reporting the effects of corporate governance on improving the quality of the financial reports. It fought to achieve its aims and supposals through a questionnaire which was distributed in Damascus stock market, and data were analyzed by using the (SPSS).